P 14 Functional activation patterns in patients with essential tremor. (May 2022) - Rodax, L.; Pfeiffer, V.; Erdmann, C.; Münte, T.F.; Nitschke, M.F.
Abstract : Introduction: Despite a significant reduction in the quality of life in patients suffering from an essential tremor (ET), the pathophysiological background of this disease is largely unknown. The cerebellum seems to be involved in the pathological process and the modulation of motor output (Nitschke 2004 (1), Popa 2013 (2) ). Previous functional imaging studies often did not induce tremor, which is problematic (Sharifi 2014 (3) ). We therefore required a typical tremor-triggering movement in patients in comparison to control-subjects using fMRI. Methods & Patients: We compared the activation patterns in fMRI images of 13 patients with age- and sex-matched controls. Clinical scores were obtained using SARA and Tetras. Subjects performed a visually guided hand movement in a block design in an fMRI setting (Philips, 3 Tesla). Participants were asked to follow the amplitude of a horizontally moving red point using their extended right arm / index finger. The resulting movement overlaid by essential tremor during performance was monitored. Data analysis was done using SPM 8. Results: Group-analysis revealed activation of fronto-parietal areas including the frontal eye field and premotor cortex and parietal areas including the inferior parietal sulcus as well as the basal ganglia. On the cerebellar level lobuli HIV-VI bilaterally, the vermis, and lobuli within the posterior hemispheres extending were activated. Patients showed a decreased activation in various brain areas compared to controls, i.e., the left basal ganglia (Fig. 1) and lobuli HIV, HVIII and IX of the cerebellum on the right side (Fig. 2). On the other hand patients showed a stronger activation of the left parietal cortex. Conclusion: The activation changes in the cerebellum further corroborate an essential role of this structure in ET pathophysiology. Moreover, we propose that some of the changes seen in patients reflect compensatory mechanisms. (1) Nitschke MF, Binkofski F, Buccino G, Posse S, Erdmann C, Kömpf D, Seitz RJ, Heide W. Activation of cerebellar hemispheres in spatial memorization of saccadic eye movements - a fMRI study. Hum Brain Mapp 2004; 22(2): 155-164. (2) Popa, T. u. a. 2013. "Cerebellar RTMS Stimulation May Induce Prolonged Clinical Benefits in Essential Tremor, and Subjacent Changes in Functional Connectivity: An Open Label Trial". Brain Stimulation 6(2): 175–79. (3) Sharifi S, Nederven A, Booij J, Rootselaar A. Neuroimaging essential in essential tremor: a systematic review. Neuroimage clinical 2014; 5: 217-231.